Green Business and Creative Accounting: A Critical Review of Sustainability Reporting in the Era of Greenwashingin - Ni Luh Anik Listya WATI; Shabrina MAULIDA; Anak Agung Erna Listya DEWI; Cynthia CYNTHIA (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:This study aims to examine the relationship between green business strategies and creative accounting practices in the context of sustainability reporting. In recent years, companies have been increasingly encouraged to project an environmentally friendly image in order to meet stakeholder demands and strengthen social legitimacy. However, companies often take advantage of the flexibility in financial reporting to construct sustainability narratives that do not fully reflect real conditions, a phenomenon known as greenwashing.Methodology:This study uses a systematic literature review approach to various national literature published in the last five years, to analyze the ambivalent role of creative accounting—as a strategic tool as well as a potential manipulative risk—in supporting or obscuring green business strategies.Findings:The results of the study show that the transparency of reporting largely determines the success of green business implementation, the integrity of management ethics, and the strengthening of sustainability reporting regulations in Indonesia.Implication:This research provides implications for the academic world, business practice, and public policy in encouraging more credible and accountable sustainability reporting.